The Marine Carbonate System at Maluku and Sulawesi Seas - iis triyulianti; I Nyoman Radiarta; Agung Yunanto; Novia Arinda Pradistya; Fikhrul Islami; Mutiara R Putri (JFMR (Journal of Fisheries and Marine Research), 2018)
Maluku and Sulawesi Seas are parts of Indonesian Large Marine Ecosystem in the east area which has an important role for Indonesian fisheries activities.  Those areas are facing the climate change phenomena that could change their marine ecosystem quality.  Marine carbonate system is very important for controlling the circulation of CO2 between the atmosphere and the ocean as well as regulating the pH value of waters. We conducted in situ measurement of marine carbonate system parameters (pH, Total Alkalinity, Total CO2 (TCO2) and pCO2) during IJEP cruise on September 2016 to analyses spatial variations of the marine carbonate system in the Northwest Monsoon period.  The results of marine carbonate system showed that in general Maluku and Sulawesi Seas are under super saturation of CO2 or acts as source of CO2 which have range value of sea surface partial of CO2(pCO2) between 280 – 500 µatm.  Spatial distribution of sea surface pH values measured with optical sensor at study sites showed varied between 8,03 – 8,15.  Measurement results of Total alkalinity (TA) by using titration method varied between 2300 – 2400 µmol/Kg meanwhile range value of TCO2 was 2300 – 2500 µmol/Kg at surface waterand it’s increased through the deep water with the range value of TCO2 was 2500 – 2800 µmol/Kg at deeper layer of water.Characteristic of marine carbonate system between Maluku  and Sulawesi Seas was different in the Southeast monsoon period indicates complex marine biogeochemistry processes influences those system.